2000
DOI: 10.1111/j.1528-1157.2000.tb00119.x
|View full text |Cite
|
Sign up to set email alerts
|

Teratogenic Effects of Antiepileptic Drugs: Use of an International Database on Malformations and Drug Exposure (MADRE)

Abstract: Summary:Purpose: The study goal was to assess teratogenic effects of antiepileptic drugs (AEDs) through the use of a surveillance system (MADRE) of infants with malformations.Methods: Information on all malformed infants (1990)(1991)(1992)(1993)(1994)(1995)(1996) with maternal first-trimester drug exposure was collected by the International Clearinghouse for Birth Defects and Monitoring Systems (ICBDMS). Cases were defined as infants presenting with a specific malformation, and controls were defined as infants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
1
6

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(104 citation statements)
references
References 20 publications
4
91
1
6
Order By: Relevance
“…Therefore, three studies used in answering these questions [7][8][9] include the offspring of mothers who took AEDs for various indications.…”
Section: Analysis Of Evidence Major Congenital Mal-mentioning
confidence: 99%
“…Therefore, three studies used in answering these questions [7][8][9] include the offspring of mothers who took AEDs for various indications.…”
Section: Analysis Of Evidence Major Congenital Mal-mentioning
confidence: 99%
“…There could be genetic differences in the prevalence of people with low activity of epoxide hydrolase, which may explain the different rates of CBZ-induced congenital anomalies. Among urogenital defects, the association between AED therapy during pregnancy and hypospadia has been reported [13]. There is less evidence about kidney involvement (hydronephrosis, renal dysplasia) [14] and prenatal AED exposure.…”
Section: Discussionmentioning
confidence: 99%
“…This is a critical period when fusion of embryonic processes forming the upper lip and palate takes place. Studies have shown a positive association between formation of cleft lip/palate and maternal medication, 6 maternal smoking, 7 and alcohol use. 8 Moreover, maternal infection, 9 and folic acid deficiency 10 may also contribute to orofacial malformations.…”
Section: Introductionmentioning
confidence: 99%